2021
DOI: 10.3390/ph14030281
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline in Ophthalmological Neurodegenerative Disease: A Comprehensive Review

Abstract: Cytidine 5’-diphosphocholine has been widely studied in systemic neurodegenerative diseases, like Alzheimer’s disease, Parkinson’s disease, and brain ischemia. The rationale for the use of citicoline in ophthalmological neurodegenerative diseases, including glaucoma, anterior ischemic optic neuropathy, and diabetic retinopathy, is founded on its multifactorial mechanism of action and the involvement in several metabolic pathways, including phospholipid homeostasis, mitochondrial dynamics, as well as cholinergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 119 publications
(80 reference statements)
0
20
0
1
Order By: Relevance
“…The treatment with LG saves a significant portion of these RGCs, and this is particularly relevant in peripheral retina, where LG treatment results in virtually complete rescue of the RGCs. According to these observations, both preclinical and clinical studies have reported RGC loss and PERG defects in glaucomatous retinas, which were protected by antioxidant treatments obtained with nutritional supplements ( Parisi et al, 2014 ; Cammalleri et al, 2020 ; Himori et al, 2021 ; Oddone et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…The treatment with LG saves a significant portion of these RGCs, and this is particularly relevant in peripheral retina, where LG treatment results in virtually complete rescue of the RGCs. According to these observations, both preclinical and clinical studies have reported RGC loss and PERG defects in glaucomatous retinas, which were protected by antioxidant treatments obtained with nutritional supplements ( Parisi et al, 2014 ; Cammalleri et al, 2020 ; Himori et al, 2021 ; Oddone et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…The effects of citicoline in diabetes appeared to be directed to a multitude of mechanisms, including glutamate excitotoxicity and oxidative stress modulation, increasing neurotrophin levels, improving the release of the neurotransmitters, enhancing the axonal transport and neuron homeostasis, promoting mitochondrial function, and modulating insulin signaling. Citicoline is involved in the sphingomyelin biosynthesis favoring the plasma membrane stabilization in the RGC axons [86,87].…”
Section: Topical Citicolinementioning
confidence: 99%
“…Cytidine 5′-diphosphocholine, better known as Citicoline, already finds its therapeutic use in systemic neurodegenerations, such as AD, PD and ischemia. In fact, citicoline, since its chemical structure resembles a precursor of phosphatidylcholine, has several action mechanisms, including phospholipid homeostasis, redox homeostasis, mitochondrial dynamics, cholinergic and dopaminergic neurotransmission [ 204 , 205 , 206 ]. Therefore, given the similarities between the neurodegeneration pattern of glaucoma and other neurodegenerative diseases (e.g., AD), citicoline has become increasingly used also in glaucoma studies showing its ability to stabilize the plasma membrane of RGC axons and to counteract glutamate excitotoxicity [ 207 ], as well as to control oxidative stress.…”
Section: Neuroprotectionmentioning
confidence: 99%